Back pain, leg swelling and a cardiac arrest: an interesting case of endocarditis. (23rd May 2014) - Donovan, Joseph; Hatcher, James; Riddell, Anna; Tiberi, Simon
Abstract : A 66-year-old woman with a history of tissue aortic valve replacement and chronic back pain presented to the emergency department with a suspected right leg deep vein thrombosis. A recent outpatient MRI had revealed discitis. A ventricular fibrillation cardiac arrest occurred in the emergency department. Cardiac output was restored on the fifth defibrillation. A transthoracic echocardiogram showed large aortic valve vegetations. Clinical impression was of infective endocarditis with cardiac arrest secondary to coronary artery embolisation. Peripheral blood cultures grew Cardiobacterium hominis, and appropriate intravenous antibiotic therapy was administered. The infected prosthetic valve was excised. The patient experienced postoperative complete heart block and a right hemisphere cerebrovascular accident, however she is now recovering well. This case describes an unusual case of infective endocarditis secondary to C. hominis, with disc, leg, coronary artery and brain septic embolisation. Infective endocarditis is an important differential diagnosis in multisystem presentations.